Analisis Loyalitas Dalam Penggunaan Layanan Elektronik Dan Pemesanan Obat Di Halodoc Dengan Kepuasan Sebagai Mediasi - Aqiilah, Rojaa Itsni; Aliyah, Kisti Nur (Jurnal Nasional Manajemen Pemasaran dan SDM, 2025)
One of the health platforms in Indonesia, Halodoc, has shown an increase in the number of visits. This article provides a deeper insight into how to improve consumer satisfaction and loyalty in using Halodoc services, including the quality of electronic services and the timeliness of delivery. The sample was taken from Halodoc users who had used the service and ordered drugs at Halodoc at least 2 times, with 139 respondents. This article uses quantitative methods and SEM-PLS models using SmartPLS 4 Software to analyze the relationship between variables and mediation effects. This study shows the results of that the quality of electronic services and the timeliness of delivery have an effect on customer satisfaction. Still, only the timeliness of delivery has a direct impact on customer loyalty. Customer satisfaction is the main factor in building customer loyalty, so Halodoc needs to improve the quality of service and delivery. This research shows that improving the overall user experience is important for retaining long-term customers.